2020
DOI: 10.1155/2020/4652898
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Serum Levels of IL-17, IL-18, TNF-α, and Lung Function Parameters in Patients with COPD, Asthma-COPD Overlap, and Bronchial Asthma

Abstract: Determination of markers of systemic inflammation is one of the important directions in the study of pathogenesis and improvement of diagnosis of chronic obstructive pulmonary disease (COPD), asthma-COPD overlap (ACO), and bronchial asthma (BA). The aim of our work was a comparative study of the features of changes in serum levels of IL-17, IL-18, and TNF-α in patients with COPD, ACO, and BA with various severity of the disease, as well as evaluation of the relationship between the level of these cytokines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 39 publications
1
28
0
1
Order By: Relevance
“… 26 In this study, we observed that 16HBECs after CSE treatment were predisposed to apoptosis (Figure 4C ), and they produced larger amounts of inflammatory cytokines, including TNF‐α, IL‐6, IL‐1β, and TGF‐β1, and airway remodeling biomarkers, including Collagen IV, Fibronectin and α‐SMA, than 16HBECs treated by none (Figure 4D–E ), which implied that airway epithelium might be injured by CSE. Regarding inflammatory factors investigated here, TNF‐α and IL‐1βare up‐regulated when inflammation cascade is initiated, 27 , 28 and IL‐6 level, mainly secreted by monocytes and macrophages, is prominently increased as inflammation severity of COPD escalates. 29 TGF‐β1, released by monocytes, expedites airway remodeling by promoting proliferation of airway smooth muscle cells, 30 which also explains why levels of airway remodeling biomarkers were increased in CSE‐exposed 16HBECs (Figure 4E ).…”
Section: Discussionmentioning
confidence: 99%
“… 26 In this study, we observed that 16HBECs after CSE treatment were predisposed to apoptosis (Figure 4C ), and they produced larger amounts of inflammatory cytokines, including TNF‐α, IL‐6, IL‐1β, and TGF‐β1, and airway remodeling biomarkers, including Collagen IV, Fibronectin and α‐SMA, than 16HBECs treated by none (Figure 4D–E ), which implied that airway epithelium might be injured by CSE. Regarding inflammatory factors investigated here, TNF‐α and IL‐1βare up‐regulated when inflammation cascade is initiated, 27 , 28 and IL‐6 level, mainly secreted by monocytes and macrophages, is prominently increased as inflammation severity of COPD escalates. 29 TGF‐β1, released by monocytes, expedites airway remodeling by promoting proliferation of airway smooth muscle cells, 30 which also explains why levels of airway remodeling biomarkers were increased in CSE‐exposed 16HBECs (Figure 4E ).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that neutrophilic inflammation, emphysematous changes and epithelial injuries might contribute to the elevated levels of NGAL in induced sputum from patients with ACO [ 128 ]. However, pro-inflammatory cytokines associated with type 1 and type 2 immunity in peripheral blood might not be useful to diagnose ACO from COPD [ 91 , 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also shown that allergic asthma can be alleviated by inhibiting IL-4R α-Stat6 and the Jagged1/Jagged2-Notch1/Notch2 signaling pathways in mice [11] . On the other hand, IL-17 exerts signi cant in uence in activating and recruiting neutrophils, enhancing in ammatory cell in ltration, participating in airway remodeling, and promoting airway hypertrophy [33][34][35][36] . γδT cells support the Th1/Th2 imbalance, implicating γδT cells in asthma development [3,37,38] .…”
Section: Discussionmentioning
confidence: 99%